Multisensor fusion for precise agriculture in paddy fields - Supod Kaewkorn; Mongkol Ekpanyapong; Manukid Parnichkun; Attaphongse Taparugssanagorn; National Science and Technology Development Agency (NSTDA), Thailand (Pathum Thani, Thailand : Asian Institute of Technology, 2021)
Nowadays, the agricultural industry has widely adopted automatic machinery to increase their productivity and reduce production costs. Labor-intensive agricultural tasks are especially targeted to be replaced by an automated robot, such as soil preparation, cultivation, fertilizing, weed control, Insecticide spray, and harvesting. Since these tasks require the robots to follow a predetermined path, one important criteria required from these robots is an accurate and precise localization, which includes XYZ position, heading, and attitude (roll and pitch tilts). This research presents a novel to design, construct a positioning and tilt angle system of agricultural machinery with high precision and low cost using an image-processing triple-laser guided (TLG) system coupled with an inertial measurement unit (IMU). The TLG system consists of a laser-pointing unit (LPU) at the base station and a laser-target unit (LTU) at the mobile robot. The robot{u2019}s XYZ position and heading are determined from the positions and the angles relative to the field of both LPU and LTU. The IMU sensor fusion determines the robot{u2019}s roll and pitch with a complementary filter. The IMU-coupled TLG system was demonstrated on an outdoor, 20 x 21 m flat field at various light intensities, and then tested in an actual paddy field in the same conditions. The paddy field testing indicates that the uneven area of the actual field does not affect the system. The overall lateral and vertical accuracies of the IMU coupled TLG system are 1.68 cm and 0.59 cm, respectively. The general heading, roll, and pitch accuracies of the IMU-coupled TLG system are 0.90{u00BA}, 0.78{u00BA}, and 0.76{u00BA}, respectively. The lateral and heading accuracies of the IMU-coupled TLG system are comparable to commercially available GNSS-INS systems from NovAtel and Trimble. On the other hand, the total cost of the IMU-coupled TLG system is only a fraction of the total cost of the commercially available localization systems.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Engineering in Mechatronics, School of Engineering and Technology
Thesis (Ph. D.) - Asian Institute of Technology, 2021
Keywords: Automatic tracking; Multisensor data fusion; Inertial navigation systems